HAK, KEDUDUKAN DAN PENYELESAIAN SENGKETA DALAM PEMBIAYAAN LEASING: STUDI MANDALA FINANCE KECAMATAN RUMBIA LAMPUNG TENGAH - Rajali Batubara; Borkat Halomoan Siregar (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2020)
This article examines rights, positions and dispute resolution in leasing financing at Mandala Finance Rumbia, Central Lampung. This research used a normative juridical approach which is a legal study carried out by a search process for various literatures and regulations that have relevance to the research problem being investigated. The results show that the rights and obligations of the parties are the same as the mechanism. This leasing financing usually refers to a standard agreement, in which the lessor has provided the form of the agreement, while the lessee is limited to take it or leave it. The consequence of this standard agreement is that the rights and obligations as well as the responsibilities contained in this agreement are more borne by the lessee. As for the settlement of disputes on leasing financing through peaceful means, Alternative Dipute Relations are consultation, consolidation, negotiation, Mediation (Arbitration), Arbitration, as well as using and using litigation with the Court. In the practice of leasing at Mandala Finance, Rumbia Subdistrict, Central Lampung, a lease that has been given legal force registered as a fiduciary card and confiscation is carried out to secure the basis of the auction, that the debtor has delivered the goods based on the letter of delivery of the goods to the creditor. Keywords: Leasing Financing, rights and obligations, and dispute resolution This leasing company is defined as a non-bank financial institution that has a function similar to that of a conventional bank, namely as a source of financing. This leasing itself can carry out financing in the form of goods, which means that these goods can be paid in installments. Leasing is an alternative for individuals or companies who lack capital to fulfill the desired goods, such as motorized vehicles. This type of research is a normative juridical approach which is a legal study carried out by a search process for various literatures and regulations that are related to the research problem being investigated. The results show that the rights and obligations of the parties are the same as the mechanism. This leasing financing usually refers to a standard agreement, in which the lessor has provided the form of the agreement, while the lessee only agrees (take it or leave it). The consequence of this standard agreement is that the rights and obligations as well as the responsibilities contained in this agreement are mostly borne by the lessee. As for dispute resolution on leasing financing through al-sulh, Alternative Dipute Relations, namely consultation, consolidation, negotiation, Mediation (Arbitration), Arbitration, as well as using and using litigation with the Court. In the practice of leasing at Mandala Finance, Rumbia District, Central Lampung, namely a lease that has been given legal force registered as a fiduciary card and confiscation is carried out to secure the basis of the auction, that the debtor has delivered the goods based on the letter of delivery of the goods to the creditor.